Studies in the creation traditions of the Septuagint, the Vulgate, the Peshitta and the Pentateuchal Targumim - Cook, Johann (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1982.